The lived experience of community college students enrolled in high risk online courses: opportunities and obstacles - Bambara, Cynthia S., author; Harbour, Clifford P., advisor (Colorado State University. Libraries, 2007)
This qualitative study explored the lived experience of community college students who were enrolled in a high risk online course (HRC). This phenomenon was examined through data collection in personal interviews with 13 students enrolled in four online courses with high rates of withdrawal or failure during five semesters from spring 2005 through summer 2006.

Isolation, Academic Challenge, Ownership, and Acquiescence emerged as the four structural themes that framed the meaning and essence of the phenomenon, Delicate Engagement. The structure Isolation described the loneliness participants felt as they experienced the HRCs. Isolation reflected the struggle of participants to establish meaningful connections with the course, their instructor, and their classmates. The structure Academic Challenge articulated participants' overwhelming feelings as they faced the content and delivery of the HRCs. This structure was heard in the voices of participants as they described their unrealistic expectations for the course, the difficulty of the academic content, the complexity of the course structure, and their frustrations with technology. Ownership emerged as a structure that portrayed how participants prized their HRC and how they embraced the challenges and demands of the course. It marked their positive stance toward the HRC and the investment they made in their class. Acquiescence emerged as the fourth structure that represented the slow and gradual ways that participants gave in to the loneliness and demands of the HRCs. It reflected the silent submissions and subtle compromises that led participants to relinquish Ownership of their HRCs. The four structures, Isolation, Academic Challenge, Ownership, and Acquiescence intermingled in positive and negative ways that led participants to survive or surrender to the HRC.

Four dimensions emerged to characterize the experience of participants: (a) empowered survivors, (b) compromised survivors, (c) reluctant surrenderers, and (d) misplaced surrenderers. The four ways in which participants survived or surrendered to their HRC experience formed the meaning and essence of the phenomenon, Delicate Engagement. It speaks to the vulnerable threads of academic and social involvement that permeated the experience of HRC participants. Connection within the HRCs was fragile, and it was too delicate to keep some participants engaged.
Keywords: attrition; community college; high-risk; online; community colleges; educational technology